Teaching poetry - Furay, H.B (Philippine Studies : A Quarterly, 1959)
This article proposes to provide some guide ropes for the teacher of literature to help in his becoming a good craftsman. As with the craftsman, this must be done, first, by knowing the job to be done, which is, in this case, a matter of knowing what the student is to derive from his study of literature; second, by knowing how to do that job, which is, in this case, a matter of knowing how to handle a written work in class so that the student's study of it is best pointed toward the end proposed.